2020
DOI: 10.1111/1750-3841.15543
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxypropyl methylcellulose or soy protein isolate‐based edible, water‐soluble, and antioxidant films for safflower oil packaging

Abstract: Edible, water‐soluble, heat‐sealable, and antioxidant films were developed from hydroxypropyl methylcellulose (HPMC) or soy protein isolate (SPI) and applied as safflower oil packaging. A 0.1 or 0.2% DL‐α‐tocopherol acetate (VE) and 0 or 0.25% oleic acid were added into film formulations to provide antioxidant and hydrophobic properties, respectively, using a 23 factorial design. Films were analyzed for appearance, microstructure, water and oil sensitivity, mechanical properties, and antioxidant functionality.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
(67 reference statements)
1
11
0
Order By: Relevance
“…As reported in other articles, the reduction of TS (Sun et al, 2017a;P erez-C ordoba et al, 2018;Agudelo-Cuartas et al, 2020;Hapsari et al, 2020;Lopes et al, 2020;Mirzaei-Mohkam et al, 2020;Zhang et al, 2020b;Dias et al, 2021;Jiang et al, 2021;Rosenbloom and Zhao, 2020), also attributed to the similarity of α-tocopherol with a plasticizer improving the mobility of the polymer chains. However, the microstructure was primarily associated with the behavior of the films for TS; that is, most of the films or coatings added with tocopherol for food presented as less rigid and less resistant than their respective controls.…”
Section: Properties Of Films and Coatingssupporting
confidence: 72%
See 1 more Smart Citation
“…As reported in other articles, the reduction of TS (Sun et al, 2017a;P erez-C ordoba et al, 2018;Agudelo-Cuartas et al, 2020;Hapsari et al, 2020;Lopes et al, 2020;Mirzaei-Mohkam et al, 2020;Zhang et al, 2020b;Dias et al, 2021;Jiang et al, 2021;Rosenbloom and Zhao, 2020), also attributed to the similarity of α-tocopherol with a plasticizer improving the mobility of the polymer chains. However, the microstructure was primarily associated with the behavior of the films for TS; that is, most of the films or coatings added with tocopherol for food presented as less rigid and less resistant than their respective controls.…”
Section: Properties Of Films and Coatingssupporting
confidence: 72%
“…Barrier properties have also been extensively studied. Some articles have reported increased water vapor permeability (WVP) (Darbasi et al, 2017;Martelli et al, 2017;Sun et al, 2017a, b;Dias et al, 2018;Agudelo-Cuartas et al, 2020;Lopes et al, 2020;Ferreira et al, 2021;Jiang et al, 2021;Yeamsuksawat and Liang, 2019) others the decrease of this parameter, attributed to the tocopherol applied to the polymer (Li et al, 2019;Mellinas et al, 2020;Mirzaei-Mohkam et al, 2020;Rosenbloom and Zhao, 2020;Yan et al, 2019;Zhang et al, 2020b).…”
Section: Usementioning
confidence: 99%
“…Lopes et al (2018) found values of WVP ranging from 8 to 12 g mm kPa -1 day -1 m -2 , and from 8 to 10 g mm kPa -1 day -1 m -2 for MFC/NFC films of Pinus sp and Eucalyptus sp., respectively. Rosenbloom and Zhao (2021) obtained values of WVP from 7 to 14 g mm kPa -1 day -1 m -2 for HPMC films reinforced with cellulose nanocrystals in concentration from 2 to 6 %.…”
Section: Water Vapor Permeabilitymentioning
confidence: 91%
“…Edible muffin liner, fruit leather wrap, and powdered drink packet were chosen for this study because they were successfully developed in our previous research (Park & Zhao, 2006; Rosenbloom & Zhao, 2021; Shih & Zhao, 2021) and are mostly easy to be adopted. Those edible packaging was made of polysaccharides, such as hydroxypropyl methylcellulose (HPMC) and starches to form strong matrices to aid functional properties (Rosenbloom & Zhao, 2021; Shih & Zhao, 2021). HPMC has high heat sealability and strong mechanical strength, is colorless, odorless, and soluble in cold water (Campos et al., 2011) and has been utilized to form into pouches and containers (Zhang et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this research was to evaluate consumer attitude, acceptability, and purchase intent toward three types of edible food packaging and their applications, including a muffin liner, cranberry pomace fruit leather wrap, and powdered drink sachet following similar film forming formulations developed in our previous studies with some modifications (Park & Zhao, 2006; Rosenbloom & Zhao, 2021; Shih & Zhao, 2021).…”
Section: Introductionmentioning
confidence: 99%